STRATEGI PEMBELAJARAN PAI DALAM MEMBANGUN KESALEHAN SOSIAL DI SISWA - Qurrata Akyuni (Institut Ummul Quro Al-Islami Bogor, 2025)
This study aims to describe and analyze effective strategies in Islamic Religious Education (PAI) for fostering students’ social piety, focusing on the supporting and inhibiting factors of their implementation. The research is motivated by the phenomenon of a gap between students’ relatively high religious literacy and the low application of social piety values in daily life. Employing a qualitative approach through a library research method, this study examines academic literature published between 2020 and 2025. Data sources include journal articles, books, and research reports from nationally and internationally accredited databases. Thematic analysis identified four main strategies that significantly contribute to developing students’ social piety: (1) value-based contextual learning that connects PAI materials with real-life experiences; (2) collaborative and participatory models that promote empathy and tolerance through direct interaction; (3) integration of digital technology with religious values, utilizing creative media to extend learning reach; and (4) synergy among schools, families, and communities to ensure the sustainability of value habituation. These strategies complement one another and are most effective when students are positioned as active subjects in the process of value internalization. Theoretically, this research enriches the literature on value-based learning by adding the dimension of cross-environment collaboration as a key success factor. Practically, the findings can serve as a guideline for PAI teachers in designing adaptive, creative, and contextually relevant learning. Further research using action research is recommended to test the effectiveness of this model across diverse cultural contexts in Indonesia.